Crude Polysaccharide Extract from the Microalga Porphyridium cruentum Improved Nonspecific Immune Responses and Resistance in Penaeus vannamei Exposed to Vibrio alginolyticus - Renata Ávila Ozório; Rafael Garcia Lopes; Felipe do Nascimento Vieira; Norha Constanza Bolívar-Ramírez; Carlos Yure Barbosa de Oliveira; Margherita Anna Antonia Maria Barracco; Marco Shizuo Owatari; Debora Machado Fracalossi; Roberto Bianchini Derner (Aquaculture Journal)
Sulfated polysaccharides (SPs), especially those with immunostimulant effects on shrimp and fish, are bioactive compounds with potential use in aquaculture. In this study, Pacific white shrimp (Penaeus vannamei) were fed diets containing 0%, 0.5%, 1.0%, 1.5%, or 2.0% crude extracts from the microalga Porphyridium cruentum for 30 days. After dietary supplementation, the shrimp were exposed to Vibrio alginolyticus, allowing the assessment of phenoloxidase activity (PO) and total hemocyte count (THC) pre- and post-challenge, as well as shrimp survival rates. Shrimp that received the 1.0% treatment had greater survival (90%) at 48 h post-challenge, while the 0% and 2.0% treatments had survival rates close to 63% in the same period. Furthermore, at 48 h post-challenge, THC was significantly greater (p < 0.05) in the shrimp that received crude extract supplementation compared to that in shrimp of the control group (0%). PO showed a proportional increase according to crude extract inclusion levels. Such dose-dependency in response to PO increases became significantly greater (p < 0.05) in the 2.0% treatment group compared to that in the 0% treatment group in the pre-challenge period and that in the 0% and 0.5% treatment groups in the post-challenge period. These results showed that crude extracts from P. cruentum could be considered immunostimulants by increasing the resistance of P. vannamei exposed to V. alginolyticus, potentially representing a major breakthrough for marine shrimp farming.